Hegel y el terror: la Revolución francesa como figura fenomenológica - Gamio Gehri, Gonzalo (Miscelánea Comillas, 2007)
The article constitutes an exploration of the figure of the Phenomenology of the Spirit (1807), corresponding to the French Revolution. Even though the problematic of the French Revolution and its conversion into the Jacobin Terror runs through the whole hegelian work, it is in the Phenomenology where this reflection finds its systematic exposition. Hegel asks himself what made it possible for the defense of the Enlightment ideals to generate into the repressive logic of Robespierre’s regime. The author resorts to the notion of negative freedom — developed in the Philosophy of the Law— as a decisive category for the hegelian comprehension of the Revolution’s political failure. Finally, Hegel examins the phenomenological outcome of revolutionary freedom in the figure of morality, as well as the possibilities of a freedom incarnated in the hegelian political thought.